Resposta :
Resposta:
[tex]a) \sqrt{36} -\sqrt{49} = 6-7=-1\\b) \sqrt[3]{8} +\sqrt{64} =2+8=10\\c) -\sqrt{100} -\sqrt[3]{64} =-10-4=-14\\d) -\sqrt[3]{125}-\sqrt[3]{-1} =-5-(-1)=-5+1=-4\\e) \sqrt[5]{1} +\sqrt{9} -\sqrt[3]{8} =1+3-2=4-2=2\\f) 100+\sqrt[5]{-32} +\sqrt[6]{0} =100+(-2)+0=100-2+0=98\\f) \sqrt[4]{16} +\sqrt[7]{1} -\sqrt[5]{-1} =2+1-(-1)=2+1+1=4\\[/tex]
Obs.: Na questão d) acredito que é [tex]-\sqrt[3]{125}[/tex] e não [tex]-\sqrt[3]{25}[/tex], até porque ná há raiz exata de
Espero ter ajudado...
Explicação passo-a-passo:
Oie, tudo bom?
a)
[tex] = \sqrt{36} - \sqrt{49} \\ = \sqrt{6 {}^{2} } - \sqrt{7 {}^{2} } \\ = 6 - 7 \\ \boxed{ = - 1}[/tex]
b)
[tex] = \sqrt[3]{8} + \sqrt{64} \\ = \sqrt[3 ]{2 {}^{3} } + \sqrt{8 {}^{2} } \\ = 2 + 8 \\ \boxed{ = 10}[/tex]
c)
[tex] = - \sqrt{100} - \sqrt[3]{64} \\ = - \sqrt{10 {}^{2} } - \sqrt[3]{4 {}^{3} } \\ = - 10 - 4 \\ \boxed{ = - 14}[/tex]
d)
[tex] = - \sqrt[3]{25} - \sqrt[3]{ - 1} \\ = - \sqrt[3]{25} - ( - \sqrt[3]{1} ) \\ = - \sqrt[3]{25} - ( - 1) \\ = - \sqrt[3]{25} + 1 \\ ≈ - 2,92 + 1 \\ \boxed{≈ - 1,92}[/tex]
e)
[tex] = \sqrt[5]{1} + \sqrt{9} - \sqrt[3]{8} \\ = 1 + \sqrt{3 {}^{2} } - \sqrt[3]{2 {}^{3} } \\ = 1 + 3 - 2 \\ = 4 - 2 \\ \boxed{ = 2}[/tex]
f)
[tex] = 100 + \sqrt[5]{ - 32} + \sqrt[6]{0} \\ = 100 + ( - \sqrt[5]{32} ) + 0 \\ = 100 + ( - \sqrt[5]{2 {}^{5} } )+ 0 \\ = 100 - 2 + 0 \\ = 100 - 2 \\ \boxed{ = 98}[/tex]
Att. NLE Top Shotta